CRIOPRESERVAÇÃO DO SÊMEN DE CATETOS (Tayassu tajacu Linnaeus, 1758) EM DILUENTE À BASE DE ÁGUA DE COCO EM PÓ (ACP-116C ®) - Silva, Mariana de Araújo da (2011)
This study aimed to test the use of powdered coconut water (ACP ®-116C) based extender in the cryopreservation of semen collared peccary, plus different concentrations of egg yolk and glycerol, as well as seeking to draw up a protocol of cryopreservation by testing different freezing curves, volumes straws for storage and post-thawing temperatures. In the first experiment, ejaculates from twelve animals were fractionated into aliquots that were diluted in Tris plus 10% egg yolk and 3% glycerol or ACP-116C ® added different concentrations of egg yolk (10 or 20%) and glycerol (1.5 and 3%), placed in liquid nitrogen and thawed after a month at 37 ° C for one minute, and their semen parameters were further evaluated for sperm motility, vigor, viability, morphology and acrosome membrane integrity and functional, place showed that ACP-116C ® plus 20% egg yolk and 3% glycerol, showed the best motility and vigor after thawing than when compared with Tris diluent (p <0.05). In the second experiment, we used the ACP-116C ® plus 20% egg yolk and 3% glycerol. After dilution the samples were divided into two aliquots, to different freezing curves freezing, slow curve (A) and fast curve (B) . The samples were packed in straws of 0.25 and 0.5ml for a week, and thawed at 37°C/ 1 min and 70°C/8s, and evaluated as in the previous experiment. There were no differences between the curves and volumes straws post thawing (p> 0.05). However, differences were observed between the volume straws and the rate of thawing at 70°C/8s (p <0.05). In conclusion, we recommend cryopreservation of collared peccary semen from ACP ® 116C plus 20% of egg yolk and 3% glycerol, using the fast curve freezing , which allows maximizing the time during the process, storage of samples in straws of 0.25 or 0.5 mL, and thawing at 37°C/60s.